Psychological Exploration of Consumer Trust in AI-Based Personalization: A Qualitative Study on the Privacy Paradox in Social Media - Hery Maulana Arif; Wiwin Riski Windarsari (Abadi Institute, 2026)
This qualitative study examines the psychological dimensions underlying the privacy paradox in the context of AI-driven personalization on social media platforms. Despite widespread awareness of privacy risks, consumers continue to engage with and benefit from personalized digital experiences, a contradictory behavior that existing quantitative models inadequately explain. Through in-depth interviews (IDI) and focus group discussions (FGD) with 24 active social media users, this study employs an interpretive phenomenological analysis (IPA) framework to explore the lived emotional and motivational experiences of individuals navigating personalization and privacy tensions. The findings reveal four core psychological mechanisms driving the paradox: (1) perceived utility as an override mechanism for privacy concerns; (2) emotional ambivalence arising from simultaneous gratitude and surveillance anxiety; (3) trust calibration shaped by platform transparency and algorithmic opacity; and (4) a learned helplessness response to structural data asymmetry. This study contributes a novel psychological typology of AI personalization consumers and offers implications for privacy-by-design frameworks, platform governance, and consumer digital literacy initiatives.